High specific energy sodium battery without negative electrode electrolyte, preparation method and application thereof

CN122992176APending Publication Date: 2026-10-27SOUTH CHINA NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611083864.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

第一,传统链状醚类溶剂(如乙二醇二甲醚、二乙二醇二甲醚等)对Na+的溶剂化能力较强,导致Na+脱溶剂化能较高,界面反应动力学缓慢,限制了电池在低温和高倍率条件下的性能发挥

Benefits of technology

[0018]与现有技术相比,本发明通过有效合理的分子结构设计合成不对称链状醚分子结构,在保证钠盐具有良好溶解能力的基础上,有效削弱了Na+与溶剂分子之间的配位作用,降低了Na+脱溶剂化能,加快了Na+在电极/电解液界面的传输与还原动力学。与此同时,不对称分子结构能够调控Na+的溶剂化结构,使阴离子更容易参与界面反应,促进形成富含NaF等无机组分的稳定SEI膜,降低界面阻抗,抑制电解液持续分解及钠枝晶生长,从而显著提高钠金属沉积/剥离的可逆性和界面稳定性;这种高比能无负极钠电池电解液的合理设计,可有效兼顾宽温域运行和长循环寿命,有效推动高能量密度、宽温域下稳定运行的无负极钠电池的发展。同时,本发明的制备方法、工艺简单、操作安全且纯度高,适于工业化。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992176A_ABST
    Figure CN122992176A_ABST
Patent Text Reader

Abstract

This invention belongs to the technical field of battery electrolytes, specifically disclosing a high-energy-density sodium-ion battery electrolyte without a negative electrode, its preparation method, and its application. The electrolyte is composed of an asymmetric chain ether and a sodium salt; the general formula of the asymmetric chain ether is [formula missing]. This invention synthesizes an asymmetric chain ether molecular structure through effective and reasonable molecular structure design, effectively weakening the Na [missing information - likely a specific chemical composition or process]. + Coordination with solvent molecules reduces Na + Desolvation energy accelerates the process of Na + Transport and reduction kinetics at the electrode / electrolyte interface. Meanwhile, the asymmetric molecular structure can modulate Na… + The solvation structure makes it easier for anions to participate in interfacial reactions, promotes the formation of a stable SEI film rich in inorganic components such as NaF, reduces interfacial impedance, inhibits the continuous decomposition of electrolyte and the growth of sodium dendrites, thereby significantly improving the reversibility of sodium metal deposition / stripping and interfacial stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of battery electrolytes, particularly high-energy-density sodium-based negative electrode battery electrolytes, their preparation methods, and applications. Background Technology

[0002] Since their commercialization, lithium-ion batteries have been widely used in consumer electronics, electronic communications, electric vehicles, and military aerospace. However, lithium resources are limited and unevenly distributed geographically, and my country relies on imports, leading to a continuous increase in raw material costs. Furthermore, the use of copper foil as the current collector in the negative electrode of lithium-ion batteries further increases manufacturing costs, limiting their large-scale application to some extent. In contrast, sodium resources are abundant, widely distributed, and inexpensive. Sodium batteries can use low-cost aluminum foil as the current collector for both the positive and negative electrodes, which helps reduce manufacturing costs. In addition, sodium and lithium are both alkali metals with similar physicochemical properties. Both sodium and lithium batteries follow the "rocking chair" energy storage mechanism and are compatible with existing lithium-ion battery manufacturing processes. Negative electrode-free sodium batteries, by eliminating the pre-storage of negative electrode active materials, can maximize battery energy density. Therefore, developing high-energy-density negative electrode-free sodium batteries has significant research value and broad application prospects.

[0003] Electrolyte is one of the key factors determining the performance of a negative electrode-less sodium battery. Compared with traditional carbonate electrolytes, ether electrolytes have better interfacial compatibility with metallic sodium, weaker solvation of sodium ions, lower desolvation energy, accelerate reaction kinetics, and facilitate the construction of a stable, low-impedance solid electrolyte interphase (SEI) film, thereby improving the battery's coulombic efficiency and cycle stability. Furthermore, ether electrolytes have a lower freezing point, which helps to broaden the battery's operating temperature range.

[0004] However, existing ether-based electrolytes still have the following defects and shortcomings: First, traditional chain ether solvents (such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, etc.) are ineffective against Na+. + The strong solvation ability of Na leads to + The high desolvation energy and slow interfacial reaction kinetics limit the battery's performance under low temperature and high rate conditions.

[0005] Second, the SEI film formed on the surface of the sodium metal anode by traditional ether electrolytes often has more organic components and less inorganic components, resulting in higher interfacial impedance. This makes it difficult to effectively suppress the continuous decomposition of the electrolyte and the growth of sodium dendrites, leading to poor reversibility of sodium deposition / stripping, low coulombic efficiency, and limited cycle life.

[0006] Third, existing ether-based electrolytes cannot simultaneously achieve high energy density and long cycle stability, especially in the absence of a negative electrode configuration. Due to the lack of an additional sodium source, the reversibility of sodium deposition / stripping has a more critical impact on battery life, and current technologies cannot effectively solve this problem.

[0007] Fourth, the low-temperature performance of existing ether-based electrolytes still needs improvement. At low temperatures, the ionic conductivity of the electrolyte decreases, the desolvation energy increases, and the battery performance deteriorates sharply, limiting the application of anode-less sodium batteries under extreme low-temperature conditions.

[0008] Therefore, how to reduce the solvation ability of ether solvents for sodium ions and regulate Na+ through reasonable molecular structure design is a key issue. + The solvation structure to promote the formation of anion-derived, inorganic-rich stable SEI film, thereby simultaneously improving the coulombic efficiency, cycle stability, energy density, and wide temperature range adaptability of the anode-free sodium battery, is the technical problem that this invention needs to solve. Summary of the Invention

[0009] To address the aforementioned technical problems, this invention provides a high-energy-density sodium-ion battery electrolyte without a negative electrode, its preparation method, and its application.

[0010] To achieve the above objectives, the present invention is implemented according to the following technical solution: The first technical solution provided by this invention is a high-energy-density sodium-ion battery electrolyte without a negative electrode, composed of asymmetric chain ethers and sodium salts; the asymmetric chain ethers have the following general structural formula: ; Wherein: R1 and R3 are respectively structural formulas C x H 2x+1 alkyl group, x is an integer in the range of 1 to 4, and R2 is a hydrogen atom or a methyl group; The sodium salt is one or more combinations of sodium difluorosulfonamide, sodium difluorooxalate borate, sodium dioxalate borate, sodium tetrafluoroborate, sodium ditrifluorosulfonamide, sodium trifluoromethanesulfonate, sodium perchlorate, and sodium hexafluorophosphate.

[0011] Furthermore, R1 and R3 are both selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, and tert-butyl.

[0012] Preferably, the asymmetric chain ether is any one of the following compounds: .

[0013] Furthermore, the concentration of sodium salt in the electrolyte of the high-energy-density, negative-electrode-free sodium battery is 1 mol / L.

[0014] The second technical solution provided by this invention is a method for preparing the above-mentioned high-energy-density sodium-ion battery electrolyte without a negative electrode, comprising the following steps: S1. Under ice bath conditions, organic solvent was added dropwise to a solution of N-methylpyrrolidone and methyl p-toluenesulfonate or a solution of N-methylpyrrolidone and ethyl p-toluenesulfonate, and stirred for 0.5 h. Then, 45 wt% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was carried out at 0 ℃ for 0.5 h, and then the temperature was raised to 50 ℃ and the reaction was carried out for 6 h. After the reaction was completed and cooled to room temperature, the white solid precipitated by deionized water was added, and the mixture was extracted with diethyl ether. The organic phases were combined and the crude product was obtained by distillation. The crude product was purified to obtain an asymmetric chain ether. S2. Dissolve the sodium salt in the asymmetric chain ether prepared in step S1 to obtain a high-energy-density sodium battery electrolyte without a negative electrode.

[0015] Preferably, in step S1, the organic solvent is any one of 2-ethoxyethanol, 2-isopropoxyethanol, ethylene glycol monotert-butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol monosec-butyl ether, ethylene glycol monopropyl ether, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, 1-methoxy-2-propanol, 2-butoxyethanol, 2-(1-methylbutoxy)ethanol, 2-(2-methylbutoxy)ethanol, and ethylene glycol monoisobutyl ether.

[0016] Further, in step S2, the purification of the crude reaction product includes the following process: first, the reaction solution is distilled to obtain the crude reaction product; then, it is washed sequentially with deionized water and saturated brine, retaining the organic phase after each wash; subsequently, the organic phase is dried with anhydrous sodium sulfate; and after filtration and distillation, the target product is obtained.

[0017] The third technical solution provided by this invention is the application of the above-mentioned high-energy-density sodium-anode-free battery electrolyte in the preparation of high-energy-density sodium-anode-free batteries.

[0018] Compared with existing technologies, this invention synthesizes asymmetric chain ether molecular structures through effective and rational molecular structure design, which effectively weakens the sodium salt's solubility while ensuring good solubility. + Coordination with solvent molecules reduces Na + Desolvation energy accelerates the process of Na + Transport and reduction kinetics at the electrode / electrolyte interface. Meanwhile, the asymmetric molecular structure can modulate Na… +The solvation structure of this invention facilitates the participation of anions in interfacial reactions, promoting the formation of a stable SEI film rich in inorganic components such as NaF, reducing interfacial impedance, and inhibiting the continuous decomposition of the electrolyte and the growth of sodium dendrites. This significantly improves the reversibility of sodium metal deposition / stripping and interfacial stability. This rational design of the high-energy-density, electrodeless sodium battery electrolyte effectively balances wide-temperature-range operation and long cycle life, effectively promoting the development of high-energy-density, stable-operating, electrodeless sodium batteries. Furthermore, the preparation method and process of this invention are simple, safe to operate, and of high purity, making it suitable for industrial application. Attached Figure Description

[0019] Figure 1 The image shows the 1H NMR spectrum of compound 1 in Example 1.

[0020] Figure 2 The image shows the carbon NMR spectrum of compound 1 in Example 1.

[0021] Figure 3 The image shows the 1H NMR spectrum of compound 2 in Example 2.

[0022] Figure 4 This is the carbon NMR spectrum of compound 2 in Example 2.

[0023] Figure 5 The image shows the 1H NMR spectrum of compound 6 in Example 3.

[0024] Figure 6 The image shows the carbon NMR spectrum of compound 6 in Example 3.

[0025] Figure 7 The image shows the 1H NMR spectrum of compound 7 in Example 4.

[0026] Figure 8 The image shows the carbon NMR spectrum of compound 7 in Example 4.

[0027] Figure 9 The image shows the 1H NMR spectrum of compound 9 in Example 5.

[0028] Figure 10 The image shows the carbon NMR spectrum of compound 9 in Example 5.

[0029] Figure 11 The image shows the 1H NMR spectrum of compound 10 from Example 6.

[0030] Figure 12 The image shows the carbon NMR spectrum of compound 10 in Example 6.

[0031] Figure 13 The image shows the 1H NMR spectrum of compound 11 in Example 7.

[0032] Figure 14The image shows the carbon NMR spectrum of compound 11 in Example 7.

[0033] Figure 15 The image shows the 1H NMR spectrum of compound 16 from Example 8.

[0034] Figure 16 The image shows the carbon NMR spectrum of compound 16 in Example 8.

[0035] Figure 17 The graph shows the performance of the Na||Cu battery assembled in Example 1 using an electrolyte of 1 M NaPF6 in EME.

[0036] Figure 18 The graph shows the performance of the Al / C||NVP negative electrodeless battery assembled in Example 1 using an electrolyte of 1 M NaPF6 in EME.

[0037] Figure 19 The graph shows the performance of the Na||Cu battery assembled in Example 2 using 1 M NaPF6 in MIPE electrolyte.

[0038] Figure 20 The graph shows the performance of the Na||Cu battery assembled in Example 3 using 1 M NaPF6 in MPrE electrolyte.

[0039] Figure 21 The graph shows the performance of the Na||Cu battery assembled in Example 4 using 1 M NaPF6 in DMPA electrolyte.

[0040] Figure 22 The graph shows the battery performance of the Al / C||NVP negative electrodeless battery assembled using 1 M NaPF6 in DMPA electrolyte in Example 4.

[0041] Figure 23 The graph shows the performance of the Na||Cu battery assembled using 1 M NaPF6 in DMPC electrolyte under low temperature -20°C conditions in Example 5.

[0042] Figure 24 The graph shows the battery performance of the Al / C||NVP negative electrodeless battery assembled using 1 M NaPF6in DMPC electrolyte under low temperature -20°C conditions in Example 5.

[0043] Figure 25 The graph shows the performance of the Al / C||NFPP negative electrode-free pouch cell assembled using 1 M NaPF6 in DMPC electrolyte in Example 5.

[0044] Figure 26The graph shows the performance of the Na||Cu battery assembled in Example 6 using 1 M NaPF6 in MNPP electrolyte.

[0045] Figure 27 The graph shows the performance of the Na||Cu battery assembled in Example 7 using 1 M NaPF6 in BME electrolyte.

[0046] Figure 28 The graph shows the performance of the Al / C||NVP negative electrodeless battery assembled in Example 7 using an electrolyte of 1 M NaPF6 in BME.

[0047] Figure 29 The graph shows the performance of the Na||Cu battery assembled in Example 8 using 1 M NaPF6 in EPrE electrolyte.

[0048] Figure 30 The graph shows the battery performance of the Al / C||NVP negative electrodeless battery assembled using 1 M NaPF6 in EPrE electrolyte in Example 8.

[0049] The above Figure 17-30 The symbol “○” in the diagram refers to the coulombic efficiency of the battery, and the symbol “●” refers to the battery capacity. Detailed Implementation

[0050] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. The specific embodiments described herein are for illustrative purposes only and are not intended to limit the invention.

[0051] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the experimental materials used in the following examples are all commercially available. Several typical asymmetric chain ethers are used to prepare high-energy-density sodium-ion battery electrolytes without a negative electrode, and then the obtained electrolytes are used to prepare high-energy-density sodium-ion battery without a negative electrode.

[0052] Example 1: Preparation of electrolyte (1 M NaPF6 in EME) suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 1 is as follows: ; Step S1: Under ice-water bath conditions, 45.06 g of 2-ethoxyethanol was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 139.67 g of methyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise, and after the addition was complete, the reaction was continued at 0 °C for another 0.5 h, followed by heating to 50 °C for 6 h. After the reaction was complete, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain ethylene glycol ethyl methyl ether (compound 1). The 1H NMR spectrum of compound 1 is shown below. Figure 1 As shown, the carbon NMR spectrum is as follows: Figure 2 As shown, the results indicate that the target product was successfully synthesized. Compound 1 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0053] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of ethylene glycol ethyl methyl ether. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a sodium hexafluorophosphate / ethylene glycol ethyl methyl ether electrolyte with a concentration of 1 mol / L (denoted as 1 M NaPF6 in EME).

[0054] Electrode fabrication and assembly of a high-energy-density sodium-ion battery without a negative electrode: Preparation of sodium vanadium phosphate (Na3V2(PO4)3) (NVP) electrodes: NVP, conductive carbon (Li400), and PVDF binder were mixed in a ratio of 80:10:10 and dispersed in N-methylpyrrolidone (NMP) solvent to prepare a uniform slurry. This slurry was then uniformly coated onto aluminum foil using a 100 μm doctor blade and subsequently vacuum-dried at 80 °C for 12 h. The electrodes were then sliced ​​to obtain electrodes with a diameter of 12 mm and an active material loading of approximately 2.5 mg / cm². -2 Or 15 mg cm -2 The electrode discs are stored in the glove box for future use; Preparation of Na||Cu batteries: In a glove box, batteries were assembled using Na metal as the negative electrode and Cu as the positive electrode, with Advantec GC-50 glass fiber and PP2500 as the separator. Na||Cu batteries were assembled using different electrolytes prepared in the following examples, and their electrochemical performance was tested at room temperature and −20 °C.

[0055] Preparation of Al / C||NVP batteries: In a glove box, commercially available carbon-coated aluminum foil (Al / C) was used as the negative electrode and the prepared NVP electrode sheet as the positive electrode, with PP2500 as the separator. Al / C||NVP batteries were assembled using different electrolytes prepared in the following examples, and their electrochemical performance was tested at room temperature and −20 °C.

[0056] like Figure 17 The figure shows the performance of a Na||Cu battery assembled using an electrolyte of 1 M NaPF6 in EME. As can be seen from the figure, the average coulombic efficiency of the battery using the 1 M NaPF6 in EME electrolyte stabilizes at 99.68% after 100 cycles.

[0057] like Figure 18 The graph shows the long-cycle performance of the Al / C||NVP electrodeless battery using 1 M NaPF6 in EME electrolyte. As can be seen from the graph, even under the harsh conditions of a 0 N / P ratio and a high-load NVP cathode, the electrodeless sodium battery assembled using 1 M NaPF6 in EME electrolyte can still stably cycle for over 150 cycles at 1.0 C, with a capacity retention rate as high as 81.08%.

[0058] Example 2: Preparation of electrolyte (1 M NaPF6 in MIPE) suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 2 is as follows: ; Step S1: Under ice-water bath conditions, 50.10 g of 2-isopropoxyethanol was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 139.67 g of methyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was continued at 0 °C for another 0.5 h, and then the temperature was raised to 50 °C for 6 h. After the reaction was completed, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 1-methoxy-2-propoxyethane (compound 2). The 1H NMR spectrum of compound 2 is shown below. Figure 3 As shown, the carbon NMR spectrum is as follows: Figure 4 As shown, the results indicate that the target product was successfully synthesized. Compound 2 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0059] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 1-methoxy-2-propoxyethane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a sodium hexafluorophosphate / 1-methoxy-2-propoxyethane electrolyte with a concentration of 1 mol / L (denoted as 1 M NaPF6 inMIPE).

[0060] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 19 The figure shows the performance of a Na||Cu battery assembled using a 1 M NaPF6 in MIPE electrolyte. As can be seen from the figure, the average coulombic efficiency of the battery using the 1 M NaPF6 in MIPE electrolyte stabilizes at 99.67% after 200 cycles.

[0061] Example 3: Preparation of 1 M NaPF6 in MPrE electrolyte suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 6 is as follows: ; Step S1: Under ice-water bath conditions, 52.07 g of 2-propoxyethanol was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 139.67 g of methyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was continued at 0 °C for another 0.5 h, and then the temperature was raised to 55 °C for 8 h. After the reaction was completed, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 1-(2-methoxyethoxy)propane (compound 6). The 1H NMR spectrum of compound 6 is shown below. Figure 5 As shown, the carbon NMR spectrum is as follows: Figure 6 As shown, the results indicate that the target product was successfully synthesized. The prepared compound 6 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0062] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 1-(2-methoxyethoxy)propane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a sodium hexafluorophosphate / 1-(2-methoxyethoxy)propane electrolyte with a concentration of 1 mol / L (denoted as 1 M NaPF6 inMPrE).

[0063] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 20 The figure shows the performance of a Na||Cu battery assembled with an electrolyte of 1 M NaPF6 in MPrE. As can be seen from the figure, the battery using the 1 M NaPF6 in MPrE electrolyte achieves an average coulombic efficiency of 99.84% after 150 cycles.

[0064] Example 4: Preparation of 1 M NaPF6 in DMPA electrolyte suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 7 is as follows: ; Step S1: Under ice-water bath conditions, 52.07 g of propylene glycol ethyl ether was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 139.67 g of methyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was continued at 0 °C for another 0.5 h, and then the temperature was raised to 55 °C for 6 h. After the reaction was completed, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 1-ethoxy-2-methoxypropane (compound 7). The 1H NMR spectrum of compound 7 is shown below. Figure 7 As shown, the carbon NMR spectrum is as follows: Figure 8 As shown, the results indicate that the target product was successfully synthesized. The prepared compound 7 was dried using molecular sieves at 25°C in a glove box with a water and oxygen content below 0.01 ppm to remove moisture.

[0065] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 1-ethoxy-2-methoxypropane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a 1 mol / L sodium hexafluorophosphate / 1-ethoxy-2-methoxypropane electrolyte (denoted as 1 M NaPF6 inDMPA).

[0066] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 21 The figure shows the performance of a Na||Cu battery assembled using an electrolyte of 1 M NaPF6 in DMPA. As can be seen from the figure, the average coulombic efficiency of the battery using the 1 M NaPF6 in DMPA electrolyte stabilizes at 99.77% after 200 cycles.

[0067] like Figure 22 The graph shows the long-cycle performance of the Al / C||NVP electrodeless battery using 1 M NaPF6 in DMPA electrolyte. Even under the harsh conditions of an N / P ratio of 0 and a high-load NVP cathode, the electrodeless sodium battery assembled with 1 M NaPF6 in DMPA electrolyte can still cycle stably for more than 400 cycles at 1.0 C with a capacity retention of 70.01%.

[0068] Example 5: Preparation of 1 M NaPF6 in DMPC electrolyte suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 9 is as follows: ; Step S1: Under ice-water bath conditions, 45.06 g of 1-methoxy-2-propanol was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 150.19 g of ethyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise, and after the addition was complete, the reaction was continued at 0 °C for another 0.5 h, followed by heating to 60 °C and reacting for 12 h. After the reaction was complete, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 2-ethoxy-1-methoxypropane (compound 9). The 1H NMR spectrum of compound 9 is shown below. Figure 9 As shown, the carbon NMR spectrum is as follows: Figure 10As shown, the results indicate that the target product was successfully synthesized. Compound 9 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0069] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 2-ethoxy-1-methoxypropane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a 1 mol / L sodium hexafluorophosphate / 2-ethoxy-1-methoxypropane electrolyte (denoted as 1 M NaPF6 inDMPC).

[0070] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 23 The figure shows the performance of the Na||Cu battery assembled with 1 M NaPF6 in DMPC electrolyte at a low temperature of −20°C. As can be seen from the figure, the battery assembled with 1 M NaPF6 in DMPC electrolyte can stably cycle 1200 times at −20°C, with an average coulombic efficiency as high as 99.95%.

[0071] like Figure 24 The figure shows the long-cycle performance of the Al / C||NVP electrodeless battery using 1 M NaPF6 in DMPC electrolyte at a low temperature of -20 °C. As can be seen from the figure, even under the harsh conditions of -20 °C, an N / P ratio of 0, and a high-load NVP cathode, the electrodeless sodium battery assembled using 1 M NaPF6 in DMPC electrolyte can still stably cycle for over 600 cycles at 0.2 C, with a capacity retention of up to 91.05%.

[0072] like Figure 25 The graph shows the long-cycle performance of an Al / C||NFPP pouch cell using a 1 M NaPF6 in DMPC electrolyte. As can be seen from the graph, the pouch cell using the 1 M NaPF6 in DMPC electrolyte exhibits a discharge capacity of 2.18 Ah when activated at 0.1 C at room temperature. Based on the overall battery weight and the discharge voltage, the energy density of the pouch cell is calculated to be as high as 202 Wh / kg. −1 The negative electrode-free pouch cell operated stably for over 200 cycles at 0.2 C, maintaining a capacity retention of 85.60% and an average coulombic efficiency of 99.87%.

[0073] Example 6: Preparation of 1 M NaPF6 in MNPP electrolyte suitable for high-energy-density sodium-based batteries and performance testing of the prepared high-energy-density sodium-based batteries. The synthetic route for compound 10 is as follows: ; Step S1: Under ice-water bath conditions, 45.06 g of propylene glycol methyl ether was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 160.71 g of propyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was continued at 0 °C for another 0.5 h, and then the temperature was raised to 60 °C for 20 h. After the reaction was completed, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 2-propoxy-1-methoxypropane (compound 10). The 1H NMR spectrum of compound 10 is shown below. Figure 11 As shown, the carbon NMR spectrum is as follows: Figure 12 As shown, the results indicate that the target product was successfully synthesized. Compound 10 was dried using molecular sieves at 25°C in a glove box with a water and oxygen content below 0.01 ppm to remove moisture.

[0074] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 2-propoxy-1-methoxypropane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a 1 mol / L sodium hexafluorophosphate / 2-propoxy-1-methoxypropane electrolyte (denoted as 1 M NaPF6 inMNPP).

[0075] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 26 The figure shows the performance of a Na||Cu battery assembled using a 1 M NaPF6 in MNPP electrolyte. As can be seen from the figure, the battery using the 1 M NaPF6 in MNPP electrolyte exhibits an average coulombic efficiency of 99.90% after 500 cycles, indicating that this electrolyte can perform reversible sodium deposition and stripping.

[0076] Example 7: Preparation of 1 M NaPF6 in BME electrolyte suitable for high-energy-density sodium-ion batteries and performance testing of the prepared high-energy-density sodium-ion batteries. The synthetic route for compound 11 is as follows: ; Step S1: Under ice-water bath conditions, 59.08 g of ethylene glycol monobutyl ether was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 139.67 g of methyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was continued at 0 °C for another 0.5 h, and then the temperature was raised to 50 °C for 6 h. After the reaction was completed, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain butyl 2-methoxyethyl ether (compound 11). The 1H NMR spectrum of compound 11 is shown below. Figure 13 As shown, the carbon NMR spectrum is as follows: Figure 14 As shown, the results indicate that the target product was successfully synthesized. Compound 11 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0077] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of hexafluorophosphate (NaPF6) and dissolve it in 1 mL of butyl 2-methoxyethyl ether. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a 1 mol / L sodium hexafluorophosphate / butyl 2-methoxyethyl ether electrolyte (denoted as 1 M NaPF6 in BME).

[0078] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 27 The figure shows the performance of a Na||Cu battery assembled with an electrolyte of 1 M NaPF6 in BME. As can be seen from the figure, the average coulombic efficiency of the battery using the 1 M NaPF6 in BME electrolyte can be stabilized at 99.02% after 600 cycles.

[0079] like Figure 28 The graph shows the long-cycle performance of Al / C||NVP batteries using 1 M NaPF6 in BME electrolyte. As can be seen from the graph, even under the harsh conditions of a 0 N / P ratio and a high-load NVP cathode, the anode-free sodium battery assembled using 1 M NaPF6 in BME electrolyte can still stably cycle for over 200 cycles at 0.5 C, with a capacity retention of up to 86.39%.

[0080] Example 8: Preparation of 1 M NaPF6 in EPRE electrolyte suitable for high-energy-density sodium-anode-free batteries and performance testing of the prepared high-energy-density sodium-anode-free batteries. The synthetic route for compound 16 is as follows: ; Step S1: Under ice-water bath conditions, 52.07 g of ethylene glycol mono-n-propyl ether was slowly added dropwise to a solution of N-methylpyrrolidone (NMP) containing 150.19 g of ethyl p-toluenesulfonate, and then stirred at 0 °C for 0.5 h. Subsequently, 45 wt.% potassium hydroxide aqueous solution was slowly added dropwise, and after the addition was complete, the reaction was continued at 0 °C for another 0.5 h, followed by heating to 55 °C for 12 h. After the reaction was complete, the reaction system was cooled to room temperature, and deionized water was added to dissolve the precipitated white solid. The solid was then extracted with diethyl ether, and the organic phases were combined and distilled to obtain the crude product. The crude product was washed successively with deionized water and saturated brine, retaining the organic phase after each wash. The organic phase was then dried with anhydrous sodium sulfate, filtered, and distilled to obtain 1-ethoxy-2-propoxyethane (compound 16). The 1H NMR spectrum of compound 16 is shown below. Figure 15 As shown, the carbon NMR spectrum is as follows: Figure 16 As shown, the results indicate that the target product was successfully synthesized. Compound 16 was dried using molecular sieves at 25°C in a glove box with water and oxygen content below 0.01 ppm to remove moisture.

[0081] Step S2: In a glove box at 25 °C with water and oxygen content below 0.01 ppm, weigh 168 mg of sodium hexafluorophosphate (NaPF6) and dissolve it in 1 mL of 1-ethoxy-2-propoxyethane. Stir overnight to ensure complete dissolution and uniform mixing, thus preparing a 1 mol / L sodium hexafluorophosphate / 1-ethoxy-2-propoxyethane electrolyte (denoted as 1 M NaPF6 inEPrE).

[0082] The electrode and battery fabrication and assembly of the high-energy-density, negative-electrode-less sodium battery are the same as in Example 1. Figure 29 The figure shows the performance of a Na||Cu battery assembled with an electrolyte of 1 M NaPF6 in EPrE. As can be seen from the figure, the average coulombic efficiency of the battery using the 1 M NaPF6 in EPrE electrolyte can be stabilized at 99.80% after 1200 cycles.

[0083] like Figure 30 The graph shows the long-cycle performance of Al / C||NVP batteries using 1 M NaPF6 in EPrE electrolyte. As can be seen from the graph, even under the harsh conditions of a 0 N / P ratio and a high-load NVP cathode, the anode-free sodium battery assembled using 1 M NaPF6 in EPrE electrolyte can still stably cycle for over 200 cycles at 0.5 C, with a capacity retention of up to 86.29%.

[0084] The results of the above embodiments demonstrate that the electrolyte containing the asymmetric chain ether molecules described in this invention exhibits excellent sodium metal compatibility, promotes uniform and stable sodium deposition, effectively suppresses dendrite growth and interfacial side reactions, thereby significantly improving the coulombic efficiency and cycle stability of the electrodeless sodium battery, providing a strong guarantee for the long-term stable operation of high-energy-density electrodeless sodium batteries. This electrolyte system achieves high coulombic efficiency (99.68%–99.90%) and long cycle life (150–1200 cycles) at room temperature, and maintains rapid sodium transport kinetics and extremely high sodium deposition / stripping reversibility (average coulombic efficiency 99.95%, stable cycling for 1200 cycles) even at −20 °C. The energy density of the electrodeless pouch cell reaches as high as 202 Wh kg. −1 In summary, this electrolyte system holds promise for applications in drones, portable electronic products, and other fields requiring high-energy-density energy storage devices, demonstrating excellent prospects for industrial application. Furthermore, even in extremely low-temperature environments, the electrolyte described in this invention maintains rapid sodium transport kinetics and high sodium deposition / stripping reversibility, effectively ensuring stable battery operation under low-temperature conditions and exhibiting excellent wide-temperature-range adaptability. It is expected to be applicable to low-temperature environments such as space, polar regions, and the deep sea.

[0085] The technical solutions of the present invention are not limited to the specific embodiments described above. Any technical modifications made in accordance with the technical solutions of the present invention fall within the protection scope of the present invention.

Claims

1. A high-energy-density sodium-ion battery electrolyte without a negative electrode, characterized in that, Composed of an asymmetric chain ether and a sodium salt; the asymmetric chain ether has the following general structural formula: ; Wherein: R1 and R3 are respectively structural formulas C x H 2x+1 alkyl group, x is an integer in the range of 1 to 4, and R2 is a hydrogen atom or a methyl group; The sodium salt is one or more combinations of sodium difluorosulfonamide, sodium difluorooxalate borate, sodium dioxalate borate, sodium tetrafluoroborate, sodium ditrifluorosulfonamide, sodium trifluoromethanesulfonate, sodium perchlorate, and sodium hexafluorophosphate.

2. The high-energy-density sodium-ion battery electrolyte according to claim 1, characterized in that, R1 and R3 are both selected from methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, and tert-butyl.

3. The high-energy-density sodium-ion battery electrolyte according to claim 1, characterized in that, The asymmetric chain ether is any one of the following compounds: 。 4. The high-energy-density sodium-ion battery electrolyte according to claim 1, characterized in that, The concentration of sodium salt in the electrolyte of the high-energy-density, negative-electrode-free sodium battery is 1 mol / L.

5. A method for preparing a high-energy-density sodium-ion battery electrolyte as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Under ice bath conditions, organic solvent was added dropwise to a solution of N-methylpyrrolidone and methyl p-toluenesulfonate or a solution of N-methylpyrrolidone and ethyl p-toluenesulfonate, and stirred for 0.5 h. Then, 45 wt% potassium hydroxide aqueous solution was slowly added dropwise. After the addition was complete, the reaction was carried out at 0 ℃ for 0.5 h, and then the temperature was raised to 50 ℃ and the reaction was carried out for 6 h. After the reaction was completed and cooled to room temperature, the white solid precipitated by deionized water was added, and the mixture was extracted with diethyl ether. The organic phases were combined and the crude product was obtained by distillation. The crude product was purified to obtain an asymmetric chain ether. S2. Dissolve the sodium salt in the asymmetric chain ether prepared in step S1 to obtain a high-energy-density sodium battery electrolyte without a negative electrode.

6. The method for preparing the high-energy-density sodium-ion battery electrolyte according to claim 1, characterized in that, In step S1, the organic solvent is any one of 2-ethoxyethanol, 2-isopropoxyethanol, ethylene glycol monotert-butyl ether, ethylene glycol monoisobutyl ether, ethylene glycol monosec-butyl ether, ethylene glycol monopropyl ether, 1-ethoxy-2-propanol, 1-propoxy-2-propanol, 1-methoxy-2-propanol, 2-butoxyethanol, 2-(1-methylbutoxy)ethanol, 2-(2-methylbutoxy)ethanol, and ethylene glycol monoisobutyl ether.

7. The method for preparing the high-energy-density sodium-ion battery electrolyte according to claim 1, characterized in that, In step S2, the purification of the crude reaction product includes the following process: first, the reaction solution is distilled to obtain the crude reaction product; then, it is washed successively with deionized water and saturated brine, retaining the organic phase after each wash; subsequently, the organic phase is dried with anhydrous sodium sulfate; and after filtration and distillation, the target product is obtained.

8. The application of the high-energy-density sodium-anode-free battery electrolyte as described in any one of claims 1-4 in the preparation of a high-energy-density sodium-anode-free battery.